The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/s2255-4971(15)30015-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Contamination in the Biopsy Path of Primary Malignant Bone Tumors

Abstract: Objective: To study factors possibly associated with tumor contamination in the biopsy path of primary malignant bone tumors. Method: Thirty-five patients who underwent surgical treatment with diagnoses of osteosarcoma, Ewing's tumor and chondrosarcoma were studied retrospectively. The sample was analyzed to characterize the biopsy technique used, histological type of the tumor, neoadjuvant chemotherapy used, local recurrences and tumor contamination in the biopsy path. Results: Among the 35 patients studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…There are different views about the preventive effect of neoadjuvant chemotherapy on tumor seeding. Some of the published studies suggest that chemotherapy has a positive effect on the control of tumor seeding . However, in line with the study of Barrientos‐Ruiz et al, we did not find a correlation between tumor seeding and neoadjuvant chemotherapy administration or the level of chemotherapy response.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…There are different views about the preventive effect of neoadjuvant chemotherapy on tumor seeding. Some of the published studies suggest that chemotherapy has a positive effect on the control of tumor seeding . However, in line with the study of Barrientos‐Ruiz et al, we did not find a correlation between tumor seeding and neoadjuvant chemotherapy administration or the level of chemotherapy response.…”
Section: Discussionsupporting
confidence: 86%
“…Davies et al reported a local recurrence of an osteosarcoma in the biopsy tract in 1993 and drew attention to the removal of biopsy tracts during the final resection of sarcomas. Some other studies announcing tumor seeding along the biopsy tract and the necessity of tract removal in bone and soft tissue sarcomas followed this study . In line with these publications, removal of the biopsy tract is a widely accepted and advised practice today .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…47 Oliveira et al published an additional cohort study on this topic. [48][49][50][51][52] However, among 30 patients who underwent surgical resection of the primary tumor without resection of the biopsy tract, there were no cases of disease recurrence noted within the in situ needle tract or other local recurrence after >4 years follow-up (pooled results of 2 studies). [48][49][50][51][52] However, among 30 patients who underwent surgical resection of the primary tumor without resection of the biopsy tract, there were no cases of disease recurrence noted within the in situ needle tract or other local recurrence after >4 years follow-up (pooled results of 2 studies).…”
Section: Incidence Of Nts After Percutaneous Biopsy Of Extremity Sarcomamentioning
confidence: 99%